Generation of monocycle efficient terahertz pulses by optical rectification in LiNBO3 at 800 nm - Ali Khumaeni; Hideaki Kitahara,; Takashi Furuya; Kohji Yamamoto; Masahiko Tani (Journal of Physics and Its Applications, 2018)
Generation of efficient terahertz (THz) pulses was experimentally made by tilted pump pulse front scheme with a Mg-doped LiNbO3 crystal. In this study, a spitfire laser (Ti:sapphire laser, 800 nm, 3 mJ, 1 kHz) was used as an optical source for the generation and detection of THz pulses. The electro-optic (EO) detection optics consisting of a ZnTe crystal (1 mm in thickness) and a balanced photodetector was used. To obtain optimum THz characteristics and pump to THz power conversion efficiency, the image of the grating was made coincides with the tilted pump pulse front. The maximum THz electric field of 8.5 kV/cm and the frequency bandwidth of 2.5 THz were achieved by using pump pulse energy of 2.4 mJ and pump pulse width of 100 fs. The THz energy of 4.15 μJ was obtained and pump-to-THz conversion efficiency was estimated to be approximately 1.73 x 10-3.